ANALISIS KEPEMIMPINAN WIDYA KANDI SUSANTI SEBAGAI CALON PETAHANA YANG GAGAL PADA PILKADA DI KABUPATEN KENDAL TAHUN 2015 - Denis Sitio; Muhammad Adnan (Journal of Politic and Government Studies, 2018)
The leadership of incumbent candidates is one of the important points in determining the acquisition of vote results in the Regional Head Election. At the end of their tenure, a public leader becomes the object of evaluation for the people who have implications for a conclusion and a political attitude, that is